Magnetic resonance imaging detected radiation-induced changes in patients with proton radiation-treated arteriovenous malformations. (26th October 2021) - Correia de Verdier, Maria; Ronne-Engström, Elisabeth; Borota, Ljubisa; Nilsson, Kristina; Blomquist, Erik; Wikström, Johan
Background: Treatment of intracranial arteriovenous malformations (AVMs) includes surgery, radiation therapy, endovascular occlusion, or a combination. Proton radiation therapy enables very focused radiation, minimizing dose to the surrounding brain. Purpose: To evaluate the presence of radiation-induced changes on post-treatment MRI in patients with AVMs treated with proton radiation and to compare these with development of symptoms and nidus obliteration. Material and Methods: Retrospective review of pre- and post-treatment digital subtraction angiography and MRI and medical records in 30 patients with AVMs treated with proton radiation. Patients were treated with two or five fractions; total radiation dose was 20–35 physical Gy. Vasogenic edema (minimal, perinidal, or severe), contrast enhancement (minimal or annular), cavitation and nidus obliteration (total, partial, or none) were assessed. Results: 26 of 30 patients (87%) developed MRI changes. Vasogenic edema was seen in 25 of 30 (83%), abnormal contrast enhancement in 18 of 26 (69%) and cavitation in 5 of 30 (17%). Time from treatment to appearance of MRI changes varied between 5 and 25 months (median 7, mean 10). Seven patients developed new or deteriorating symptoms that required treatment with corticosteroids; all these patients had extensive MRI changes (severe vasogenic edema and annular contrast enhancement). Not all patients with extensive MRI changes developed symptoms. We found no relation between MRI changes and nidus obliteration. Conclusion: Radiation-induced MRI changes are seen in a majority of patients after proton radiation treatment of AVMs. Extensive MRI changes are associated with new or deteriorating symptoms.